2009
DOI: 10.4103/0973-8258.59735
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of subacute oral administration of cypermethrin in rats with special reference to histopathological changes

Abstract: Pyrethrins are obtained from the flowers of Chrysanthemum cinerarifolium. These are strong insecticides with low mammalian toxicity. The toxic effects of pyrethroid cypermethrin were studied using various biochemical parameters along with histopathological changes in a 30-day study in Wistar rats. The rats were divided into two groups. Rats of the test group were given sublethal doses of cypermethrin (14.5 mg/kg) by gavage once daily for 30 days and the control rats were given an equal volume of the vehicle. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…Maximum decline produce hepatotoxicity. High plasma concentrations of st of 29.2% was observed on 21 day of treatment which ALT and AST are considered as an index of liver was comparatively higher than fenvalerate (20.5%) damage [22]. An increase of aminotransferase activity and sodium nitrate (7.69%) exposed groups.…”
Section: Introductionmentioning
confidence: 92%
“…Maximum decline produce hepatotoxicity. High plasma concentrations of st of 29.2% was observed on 21 day of treatment which ALT and AST are considered as an index of liver was comparatively higher than fenvalerate (20.5%) damage [22]. An increase of aminotransferase activity and sodium nitrate (7.69%) exposed groups.…”
Section: Introductionmentioning
confidence: 92%
“…Histopathological study revealed that hepatocytes undergo atrophy and sever necrosis and destruction with infiltration of polymorph nuclear leucocytes dependent manner. Similarly, (24) were marked diffuse necrosis of hepatic tissue in all cypermethrin treated in rats. While the evident that cypermethrin produced hemorrhage and congestion were found in liver, agree with (12).…”
Section: Discussionmentioning
confidence: 77%
“…These changes may be attributed to increased peroxidation of polyunsaturated fatty acids. Previous studies have suggested that cypermethrin induces histopathological changes in liver [46,65]. These changes are possibly due to oxidative stress induced by cypermethrin toxicity.…”
Section: Discussionmentioning
confidence: 93%